Echinacoside exerts antidepressant-like effects through enhancing BDNF-CREB pathway and inhibiting neuroinflammation via regulating microglia M1/M2 polarization and JAK1/STAT3 pathway - Lu, Renrui; Zhang, Li; Wang, Huihui; Li, Meng; Feng, Weisheng; Zheng, Xiaoke (Frontiers in Pharmacology, 2023)
The present study was performed to investigate the antidepressant effect of Echinacoside (ECH) using chronic unpredictable mild stress (CUMS) induced depression mice and lipopolysaccharide (LPS)-stimulated N9 microglial cells. CUMS treatment was performed on C57BL/6 mice for 28 days, followed by gavaging with different doses of ECH (15 and 60 mg/kg) for 21 consecutive days. Sucrose preference test (SPT), open field test (OFT), tail suspension test (TST), and forced swimming test (FST) were measured to assess the effects of ECH on CUMS-Induced Depressive-Like Behaviors. After that, the pathological changes of hippocampus were determined by Hematoxylin and eosin (HE) staining and Nissl staining; the neurotransmitters, pro-inflammatory cytokines and indoleamine 2,3-dioxygenase (IDO) levels, and the hypothalamic–pituitary–adrenal (HPA) axis activity were determined by enzyme linked immuno sorbent assay (ELISA); Iba 1were evaluated by Immunofluorescence assay; Key protein expression levels of CREB/BDNF signal pathway were measured by western blotting. Subsequently, N9 cells were stimulated with 1 μg/ml LPS to induce N9 microglia activation, and were treated with 5-20 μM of ECH for 24h. After that, the levels of NO, interleukin (IL)-1β, IL-6, tumor necrosis factor alpha (TNF-α), IL-4, IL-10, and transforming growth factor beta (TGF-β) in N9 cell culture supernatants were measured by enzyme-linked immunosorbent assay (ELISA) kits; morphology and Iba 1 expression level were observed by high-content screening assay; the M1 markers of CD11b, CD86 and M2 markers of CD206 were analyzed by imaging flow cytometry. Results show that treatment with ECH reversed CUMS-increased immobility time in OFT, TST, FST and reversed CUMS-reduced sucrose preference in SPT. In addition, ECH reduced the levels of pro-inflammatory cytokines and Iba 1. Moreover, ECH significantly increased p-CREB/CREB ratio and BDNF level in hippocampus. Furthermore, ECH reduced the secretion of inflammatory factors and inhibited microglia M1 polarization in N9 cells. In conclusion, ECH may be beneficial for the treatment of depression diseases through regulating the microglia balance by inhibiting the polarization of microglia to M1 phenotype, and improving hippocampal neurogenesis by the CREB-BDNF signaling pathway.